Association between One-Hour Post-Load Plasma Glucose Levels and Vascular Stiffness in Essential Hypertension - Sciacqua, Angela; Maio, Raffaele; Miceli, Sofia; Pascale, Alessandra; Carullo, Giuseppe; Grillo, Nadia; Arturi, Franco; Sesti, Giorgio; Perticone, Francesco (PloS one, 2012)
Pulse wave velocity (PWV) is a surrogate end-point for cardiovascular morbidity and mortality. A plasma glucose value ≥155 mg/dl for the 1-hour post-load plasma glucose during an oral glucose tolerance test (OGTT) is able to identify subjects with normal glucose tolerance (NGT) at high-risk for type-2 diabetes (T2D) and for subclinical organ damage. Thus, we addressed the question if 1-hour post-load plasma glucose levels, affects PWV and its central hemodynamic correlates, as augmentation pressure (AP) and augmentation index (AI). We enrolled 584 newly diagnosed hypertensives. All patients underwent OGTT and measurements of PWV, AP and AI. Insulin sensitivity was assessed by Matsuda-index. Among participants, 424 were NGT and 160 had impaired glucose tolerance (IGT). Of 424 NGT, 278 had 1-h post-load plasma glucose <155 mg/dl (NGT<155) and 146 had 1-h post-load plasma glucose ≥155 mg/dl (NGT≥155). NGT≥155 had a worse insulin sensitivity and higher hs-CRP than NGT<155, similar to IGT subjects. In addition, NGT ≥155 in comparison with NGT<155 had higher central systolic blood pressure (134±12 vs 131±10 mmHg), as well as PWV (8.4±3.7 vs 6.7±1.7 m/s), AP (12.5±7.1 vs 9.8±5.7 mmHg) and AI (29.4±11.9 vs 25.1±12.4%), and similar to IGT. At multiple regression analysis, 1-h post-load plasma glucose resulted the major determinant of all indices of vascular stiffness. Hypertensive NGT≥155 subjects, compared with NGT<155, have higher PWV and its hemodynamic correlates that increase their cardiovascular risk profile.